First cases of combined full robotic partial nephrectomy and colorectal resections: Results and new perspectives. Issue 5 (24th June 2020) - Piccoli, Micaela; Pecchini, Francesca; Esposito, Sofia; Sighinolfi, Chiara; Gozzo, Davide; Trapani, Vincenzo; De Carne, Cosimo; Rocco, Bernardo Maria Cesare
Abstract: Background: Nowadays the robotic platform is widespread in general surgery, urology, and gynecology. Combined surgery may represent an alternative to sequential procedures and it allows the treatment, at the same time, of coexisting lesions; in this perspective, full‐robotic multiorgan surgery is starting to gain interest from surgeons worldwide. Methods: Between April and June 2019, two patients presenting with synchronous colorectal and kidney cancers underwent, respectively, full‐robotic right colectomy with right partial nephrectomy and anterior rectal resection with left partial nephrectomy. Surgeries were performed by both the general surgery and urology team. Results: No intraoperative complications were registered and the postoperative course was uneventful in both cases. Conclusions: Combined multiple organ surgery with full robotic technique is safe and offers oncological adequate results. A multi‐team surgical pre‐planning is mandatory to reduce invasiveness and operative time. To the best of our knowledge, these are the first reports of full robotic partial nephrectomy combined with colorectal procedures.